A gas adsorption porosimetry analysis of Portland cement prepared by compaction vs. compaction with indirect ultrasonic agitation - Nader Azizi; Yltze P Cubas; Maria F Orellana (University Library System, University of Pittsburgh, 2014)
Background: Mineral trioxide aggregate (MTA), is commonly used in endodontic and restorative procedures. Objective: Our objective was to introduce gas adsorption porosimetry as a viable method for evaluation of general porosity and specific pore characteristics of set Portland cement used in substitute for MTA, to investigate the effect of two different obturation methods (compaction and compaction in conjunction with indirect ultrasonic agitation of the cement paste), and to evaluate the correlation between the specific pore characteristics to compressive strength in general. Material and Methods: Portland cement samples were prepared and divided into two groups based on compaction techniques. An initial stereomicroscopic evaluation was done to assess any differences in appearance of pores randomly selected from either of the two experimental groups.  Specific pore characteristics and compressive strength were quantified by a gas adsorption porosimeter and an Instron universal testing machine. A two tailed student t-test was used for statistical comparison of data, and a regression analysis was done to evaluate the correlation between each specific pore characteristic and compressive strength in general. Results: The gas porosimetry method provided measurable values relating to specific pore characteristics of Portland cement.  The stereomicroscopy evaluation revealed marked differences between samples from the two groups, namely visibly larger pores both on the outside surface and in cross-sections of specimens prepared by the indirect ultrasonic activation method.  Conclusions: Gas adsorption porosimetry is a feasible method for evaluation of specific pore characteristics of Portland cement and potentially other dental materials as well.